Integrasi Agama dan Budaya dalam Ritual Hitirima Masyarakat Negeri Pelauw Maluku Tengah - M Asrul Pattimahu; Abdul Manaf Tubaka (DIALEKTIKA, 2021)
The purpose of writing this article is to explain the integration of religion and culture in the implementation of the Hitirima ritual in the Muslim community in the State of Pelauw. How the Hitirima ritual is carried out in the context of religious and cultural relations as a model for the diversity of the Muslim community in Maluku is the main problem in this article. Sources of data were obtained through participatory observations and in-depth interviews with a number of religious leaders, traditional leaders and community leaders in the land of Pelauw. This study confirms that (1) the mono-dualistic cosmology of the Maluku community contributes to the strength of integration between Islamic values and local cultural values. (2) The religious pattern of the Hatuhaha community, especially the Pelauw country, emphasizes the importance of the position of local wisdom values in this case the Hitirima tradition and Islamic values as the construction of religious models of shared social life. (3) there is a strong relationship between religion and culture in the Hitirima ritual which can be seen from the use of attributes where there is a combination of Islamic culture and customs, prayers that are read during rituals, as well as religious values that are internalized from the implementation of the ritual. Keywords: Integration, Religion and Culture, Hitirima Ritual, Pelauw Society